Oxyura vittata (Philippi, 1860) (Aves, Anatidae): Range extension and first record from the Upper Paraguay basin, Brazil - Severo-Neto, Francisco [UNESP]; Leuzinger, Lucas; de Faria, Sandro Paulino (Pensoft Publishers, 2017)
This note extends the range of Oxyura vittata (Philippi, 1860) to the Upper Paraguay basin in the Brazilian Pantanal and presents the first record of this species from Mato Grosso do Sul state.
Keywords: Lake duck; Migratory birds; Pantanal